Chirality and life a short introduction to the early phases of chemical evolution - Flügel, Rolf M. (Springer eBooks., 2011)
This book presents the fascinating formation of the first simple bioorganic molecules and describes the hidden aspects of chiral compounds, which raise questions on the molecular beginnings of life. The occurrences of extraterrestrial, non-standard amino acids in meteorites are dealt with in detail, as well as their subsequent transfer to proteinogenic amino acids. The concept of asymmetric organo-catalysis for the synthesis of carbohydrates and ribonucleosides are considered. The notion of a single amino acid that functions as an enzyme is developed. Attempts to simulate ancient world scenarios are critically reviewed. There is a special focus on ribozymes and the resulting RNA world. Combinations of different world scenarios are discussed in view of an on-going evolution. The currently most plausible hypotheses and visions of ancient world scenarios that led to today?s DNA world are also provided. Included is a pre-cellular world of viruses that is presented for the first time.